2008
DOI: 10.1111/j.1742-4658.2008.06512.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics, stability and iron‐binding activity of frataxin clinical mutants

Abstract: Human frataxin is a mitochondrial protein whose deficiency is associated with the neurodegenerative disorder Friedreich ataxia (FRDA; OMIM 229300), a pathology characterized by neuronal death, cardiomyopathy and diabetes [1]. At the molecular level, the disease involves iron homeostasis deregulation and an impairment of the biosynthesis of iron-sulfur proteins [1][2][3][4]. The majority of FRDA patients (> 95%) are homozygous for a GAA repeat expansion within the first intron of the frataxin gene [5,6]. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(85 citation statements)
references
References 33 publications
9
76
0
Order By: Relevance
“…8). As reported previously [14], the C-terminal domain of wild-type FXN exhibits rather uniform values of the relaxation rates along the protein sequence, a sign of a compact globular protein. Indeed, the <hnNOE> value is 0.81 AE 0.07, with only the C-terminus experiencing significantly lower values than average (Fig.…”
Section: Ctr Mutants Exhibit An Increment Of Internal Motions On Sevementioning
confidence: 51%
See 3 more Smart Citations
“…8). As reported previously [14], the C-terminal domain of wild-type FXN exhibits rather uniform values of the relaxation rates along the protein sequence, a sign of a compact globular protein. Indeed, the <hnNOE> value is 0.81 AE 0.07, with only the C-terminus experiencing significantly lower values than average (Fig.…”
Section: Ctr Mutants Exhibit An Increment Of Internal Motions On Sevementioning
confidence: 51%
“…This increase in motions is globally distributed, suggesting a manifestation of cooperativity in dynamics. Protein dynamics of human FXN in the picosecond/ nanosecond range were previously studied by NMR [14,38]. Longitudinal and transverse relaxation rates and hnNOE indicated that FXN behaves as a rather rigid and compact globular protein with internal motions on the picosecond/nanosecond timescale at both termini.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is, however, unlikely that frataxins directly protect mitochondrial DNA, because their levels of expression would be insufficient for such a function. Some clinically occurring mutations have the effect of reducing thermodynamic stability with a consequent increasing likelihood of proteolytic digestion [30,41,42].…”
Section: ■ the Structure Of Frataxinsmentioning
confidence: 99%